Assessing the medication abortion drug dispensing practices of private sector chemists through mystery client (Round IV). - Tamang,Anand (2018)
SUMMARY: A total of 230 pharmacy outlets, randomly sampled from 21 districts were observed by trained male and female researchers who acted as abortion clients (mystery clients). The main objective of the mystery client observation was to assess the dispensing practices of medication abortion pills (mifepristone and misoprostol) by pharmacy workers (PW) who were stocking Medabon. Each of the sampled pharmacy outlets (PO) was visited twice at different time periods by a male and female mystery client researcher/observer (MCO). The male MCO was trained to pose as spouse of married woman who was currently pregnant at 8-9 weeks gestation (LMP), whereas each female MCO was trained to present herself as pregnant with LMP 11-12 weeks at one PO and pregnant with 13-14 weeks LMP at the other pharmacy outlet. Immediately after completing the observation, MCOs filled-up a selfadministered exit questionnaire in the presence of the research supervisors that recorded key behavioral factors of PO regarding MA pills dispensing practices and quality of care maintained by them. Approximately, less than a third of the POs observed were ordinary pharmacies (63%) and a third comprised of pharmacies having a clinic facility (32%). Few POs (5%) were hospital based pharmacy outlets. As regards the sex of the pharmacy workers who had served the MCOs, three fifths were attended by a male provider while in the remaining two-fifths were served by a female PW. Approximately four out of five PWs (both exposed to HR orientation and not oriented) confirmed the gestational age from their clients first. Most of the MA pills offered by PW were in combipack (about 90%). More than two third PWs (68.2%) offered the government registered MA drug. A significant proportion of PW did not mentioned about the complication to their male clients as well as female clients posing 11-12 weeks LMP. A higher proportion of PW did not suggest their clients where to go in case of complications. Most of PW (> 80%) did not provided any information on the ways to confirm abortion completion. The large majority of the PWs did not provide written instructions on MA use. Only about a quarter of the PW (28%) write the dose and time of the intake/administration of the pills on a piece of paper. MA pills were offered to 43 percent of the male MCO, 15 percent of the male MCO were refused the pills while 40 percent of male MCOs were referred by the PWs elsewhere to obtain the same. Comparatively, a slightly higher percentage of pharmacy workers who were oriented on harm reduction dispensed MA pills to male clients (46%) than those not oriented (43%). Among the female MCO who had posed as pregnant with 11-12 weeks' LMP, close to one fourth (23%) were dispensed with MA pills and one-eight (12%) were denied the pills. On the other hand, a large segment of the female MCOs were referred elsewhere. Female clients' referral was relatively higher for those posing as 13-14 weeks LMP and by pharmacy worker exposed to harm reduction training (80%). Male pharmacy workers were more likely to provide MA pills than the female pharmacy workers irrespective of the gestation age posed by the MCOs. On the other hand, a higher percentage of female pharmacy workers (67%) than the male PWs (31%) oriented to the training referred their male MCOs to visit safe abortion service (SAS) facilities or denied the pills (17% vs 14%). Comparatively a lower proportion of female PWs (40%) not oriented to training referred male MCOs or denied to dispense MA pills to men (24%). The providers who were exposed to HR training did not dispensed MA pills to their female clients (MCOs) of higher gestation (13-14 weeks). A higher percentage of POs not-exposed to orientation made referrals of male clients than those who had received the orientation. In contrast, more than a half of the female MCOs (56%) posing themselves as 11-12 weeks LMP and nearly half (48%) posing as 13-14 weeks LMP were referred by the POs elsewhere on the ground of high gestational LMPs. Similarly, more than a third (34.7%) female clients posing as pregnant at 11-12 weeks' gestation and nearly a half (48%) female clients posing 13-14 weeks of gestation were suggested to visit an accredited safe abortion service (SAS) center. High gestational LMP was the primary reason for denial to dispense MA pills to female MCOs. Whereas for the male MCOs, the providers insisted on bringing their spouses (45%), while another 28 percent were sent back saying that they need to produce physician's prescriptions for MA use. Interestingly, roughly one in four (23%) of the male MCOs were advised to produce USG results to re-confirm the gestational age. The price charged ranged from Rs. 200 to more than Rs. 2500. Altogether 107 MCOs (71 male and 36 female) out of 143 MCOs who were offered the MA pills bought the pills (MCOs were instructed to purchase MA within the price range of Rs 800). Some of the POs also offered pain management drugs and 8 providers offered vitamins to their clients together with MA pills. Majority of the MA pills offered at PO were in combi-packs (about 90%). As many as 14 brands of combi-packs (mifepristone 400 mg x 1 and misoprostol 200 mcg x 4) were sold to MCOs and only one brand of separate pack was offered to few MCOs. Although all PWs who had received orientation were encouraged by PSI to dispense Medabon, nearly all of them stocked other brands of MA pills. However, Medabon (35.5%) was relatively the most popular brand offered by the pharmacy workers, followed by Meriprist (15.2%) and MTP Kit (9.3%). Approximately, four-fifth of the providers (both oriented and not oriented) instructed their male and female clients about when to take the first dose (mifepristone) and the second dose of misoprostol tablets. However, not all male MCOs received correct information on the drug regimens, especially on misoprostol use. Only 68% of oriented and 53% not oriented PWs gave correct information on the drug regimen to male clients. Similarly, 76% oriented and 57% un-oriented PWs provided accurate information to their male clients on the route of administration. PWs discussed with their male clients about what to expect during abortion process; possible side effects that may occur with the pills and complications (such as excessive bleeding, severe lower abdominal pain). MCOs were also told where to go in case of complications and the need for a follow up visit to confirm the completeness of the abortion. Only about a quarter of the oriented and not-oriented POs (28% each) provided written instructions to their male MCOs. The corresponding percentage for female MCOs were low. Some of the PWs asked their clients whether they understood the instruction clearly and if they have any questions. Very few PWs showed leaflets on MA while dispensing MA pills to clients while some showed strip of MA at the time of explaining when and which MA pill to be taken. Very few PWs also provided MA leaflet to the MCO. Only few pharmacy outlets (PO) had visible communication materials on medication abortion such as poster, calendar, dangler and flipchart etc. Conclusions & Discussions Despite the policy restrictions, over the counter (OTC) provision of MA pills (combined use of mifepristone and misoprostol tablets) by pharmacy workers, it is not an uncommon practice in the country. PSI/Nepal have been providing harm reduction training to pharmacy workers basically to ensure that they abstain from irrational dispensing of MA pills, rather refer clients to accredited Safe Abortion Sites, adhere to the recommended regimens, routes of misoprostol administration and advise on potential side effects with MA use. The present mystery client observation study has demonstrated the fact that pharmacy worker offer MA pills to clients over the counter. More male pharmacy workers than female pharmacy workers offered the MA pills over the counter to the mystery client observers, sometimes even to women with higher gestational LMP. The effectiveness of orientation training on pharmacy worker's behavior in rational MA pills dispensing practice is evident from the study. This is more apparent among the female provider/pharmacy workers exposed to PSI orientation.